Principals' perceptions of the management of staff appraisal in schools. - Blaauw, Lindiwe Ellen (Rhodes University, Faculty of Education, Department of Education, 2000)
Teacher appraisal has long been a contentious and contested area in educational management. The recent implementation of a new system of appraisal in Eastern Cape Schools has led to renewed interest in the role and management of appraisal. The objective of this study was to investigate principals' perception of the management of staff appraisal. An interpretive paradigm was adopted and the research is a case study of four secondary schools in Port Elizabeth. Two methods were used in collecting data, namely, questionnaires and interviews. The content comparative method was used to analyse the data. The findings of this study showed areas of continuities and discontinuities with the literature and the new document on appraisal. There is a clear understanding among the principals interviewed that staff appraisal should be used to assess individual teacher performance and that it should also be developmental. There is clear support from the principals on the involvement of other stakeholders. They see the process as transformative and participatory. They find it acceptable and are willing to be involved. However, the findings also indicate a lack of readiness on the part of the principals to fully embrace a fully participative and developmental approach to appraisal. On the strength of these findings I conclude the thesis by making recommendations for policy, principals, teachers and for future researchers in the field.
Keywords: Educational evaluation; Teachers -- Rating of